The Double Global Domination Number of a Graph - Soner, N. D.; Chaluvaraju, B.; Janakiram, B. (The Journal of the Indian Mathematical Society, 2003)
Let G=(V, E) be a graph. A double dominating set D of G is a double global dominating set, if D is also a double dominating set of ¯G. The double global domination number Î³dg(G) of G is the minimum cardinality of a double global dominating set of G. In this paper, a study on this new parameter is initiated.